Kinetic Alfvén waves and particle response associated with a shock‐induced, global ULF perturbation of the terrestrial magnetosphere. Issue 21 (14th November 2015) - Malaspina, David M.; Claudepierre, Seth G.; Takahashi, Kazue; Jaynes, Allison N.; Elkington, Scot R.; Ergun, Robert E.; Wygant, John R.; Reeves, Geoff D.; Kletzing, Craig A.
Abstract: On 2 October 2013, the arrival of an interplanetary shock compressed the Earth's magnetosphere and triggered a global ULF (ultra low frequency) oscillation. The Van Allen Probe B spacecraft observed this large‐amplitude ULF wave in situ with both magnetic and electric field data. Broadband waves up to approximately 100 Hz were observed in conjunction with, and modulated by, this ULF wave. Detailed analysis of fields and particle data reveals that these broadband waves are Doppler‐shifted kinetic Alfvén waves. This event suggests that magnetospheric compression by interplanetary shocks can induce abrupt generation of kinetic Alfvén waves over large portions of the inner magnetosphere, potentially driving previously unconsidered wave‐particle interactions throughout the inner magnetosphere during the initial response of the magnetosphere to shock impacts. Key Points: An interplanetary shock impact drives kinetic Alfvén waves The data imply prompt kinetic Alfvén wave formation throughout the inner magnetosphere Low‐energy particle advection due to a shock‐induced ULF wave is studied